Efectos de un programa de Musicoterapia en el fortalecimiento de la Inteligencia Emocional, en un grupo de adultos mayores del Centro Día “Tierra de Saberes” de la ciudad de Bogotá. (2019)
The following paper describes a Music Therapy intervention that focused on strengthening the Emotional Intelligence of the elderly, the exercise took place in Bogotá at the Centro Día “Tierra de Saberes”, and involved 11 participants, including men and women between the ages of 60 and 76 years old; a grand total of 10 encounters of 2 hours each were performed, during a 4 month period. The activity was carry out in a group format, and mainly focused on Working with songs following the Abordaje Plurimodal (APM) (Schapira, 2007), specially regarding the Collective Singing, Creation, The Evocative Induction Conscious, The Evocative Induction Unconscious, Improvisation, Free Association through singing, and Songs Interweaving (Trama de canciones). Moreover, This research was based on the principles of Acceptation Therapy (ACT Therapy) (Barraca, 2009), which belongs to the group of therapies of Cognitive Behavioral Approach (Ramos, 2008), and the concept of Emotional Intelligence (Goleman, 1995); in this research has emphasized on the self-awareness, understood as the achievement of modulating emotions and therefore modifying their own behavior (Gómez y Calleja, 2016). The investigation design was a group case study and the methodological framework was based on the investigation-participatory action design. The qualitative data obtained through out the experience was validated through triangulation of the evidence such as audio and video tape of the process, the analysis of each session and semi-structured interview with the participants, described in a matrix specially made for this research, which allowed to correlate the emotional, cognitive, verbal and musical-sonorous aspects specific of the Music Therapy. As a result, the research found that the Music Therapy provides elements that contribute to the strengthening of the Emotional Intelligence in the elderly on a preventive stage - that is to say, in which the participant does not experience a symptom picture of deep emotional imbalance - that achieved healthier intrapersonal and interpersonal relationships and manage their emotions, thus contributing to individual and social welfare.